PENGARUH PENGGUNAAN KOIL RACING TERHADAP PERFORMA MESIN 4 LANGKAH 125 CC - Herbanu Kuntoro Jati; Ranto Ranto; Valiant Lukad Perdana Sutrisno (Nozel : Jurnal Pendididikan Teknik Mesin, 2024)
The aims of this study are : (1) To determine the effect of using racing coil on the power generated of 4 step motorcycle 125 cc, (2) To determine the effect of using racing coil on the torque generated of 4 step motorcycle 125 cc. The research method used is experimental. The data of this research was obtained by taking measurements on sample of Honda Blade 125 FI 2014 motorcycle. The independent variables were standard ignition coil and racing ignition coil. The variables were maximum shaft power dan maximum shaft torque measured using a dynamometer. The data obtained were then analyzed using quantitative descriptive techniques by describing in the form of graphs and tables. The result of the study are : (1) The use of racing ignition coil has a higher effect on the power produced. (2) The use of racing ignition coil has a lower effect on the torque produced.